The International Committee of the Red Cross and its mandate to protect and assist: law and practice - Shucksmith, CL (2015)
It is 150 years since the establishment of the International Committee of the Red Cross (ICRC), following Henry Dunant’s experiences during the aftermath of the Battle of Solferino. It is 100 years since the commencement of the Great War: if we think about a ‘traditional’ battlefield, what images come to mind? Perhaps one imagines soldiers in uniform, tanks, guns and trenches. Do the emblems of the International Red Cross and Red Crescent Movement (IRCRCM) feature in the imagined conflict scenario? Now imagine the conflicts happening today in, for example, Syria, Mali, Democratic Republic of Congo (DRC) and Ukraine. In these conflicts, soldiers mingle with civilians in towns, armoured vehicles and open backed trucks transport non- uniformed soldiers between conflict areas and weapons include, amongst others, improvised explosive devices, suicide bombers and sexual violence. Nevertheless the emblems of the IRCRCM continue to emblazon the uniforms of medical personnel and their equipment, vehicles and aid boxes.